2021
DOI: 10.1158/2326-6066.cir-20-0358
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Lipoproteins Promote Resistance to Cancer Immunotherapy Independent of Patient Obesity

Abstract: Antitumor immunity is impaired in obese mice. Mechanistic insight into this observation remains sparse and whether it is recapitulated in patients with cancer is unclear because clinical studies have produced conflicting and controversial findings. We addressed this by analyzing data from patients with a diverse array of cancer types. We found that survival after immunotherapy was not accurately predicted by body mass index or serum leptin concentrations. However, oxidized low-density lipoprotein (ox-LDL) in s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 56 publications
1
24
1
Order By: Relevance
“…In contrast, the melanoma tumors examined did not display this relationship. Finally, our analysis of CD8+ TILs from renal cancer patients showed that obesity is associated with reduced frequencies of PD-1 high CD8+ TILs ( 18 ), which differs from the lack of an association between obesity and PD-1+CD8+ TILs found in a combined cohort of melanoma and breast cancer patients ( 30 ). Collectively, these findings illustrate that immune responses to solid tumors can vary greatly between tumor types.…”
Section: Re-examining the Obesity Paradox Paradigm In Cancer Immunotherapycontrasting
confidence: 70%
See 3 more Smart Citations
“…In contrast, the melanoma tumors examined did not display this relationship. Finally, our analysis of CD8+ TILs from renal cancer patients showed that obesity is associated with reduced frequencies of PD-1 high CD8+ TILs ( 18 ), which differs from the lack of an association between obesity and PD-1+CD8+ TILs found in a combined cohort of melanoma and breast cancer patients ( 30 ). Collectively, these findings illustrate that immune responses to solid tumors can vary greatly between tumor types.…”
Section: Re-examining the Obesity Paradox Paradigm In Cancer Immunotherapycontrasting
confidence: 70%
“…Two recent studies did not observe positive associations between leptin concentration and the frequency of PD-1+CD8+ T cells. Khojandi et al found no significant associations (positive or negative) between either BMI or plasma leptin concentrations and PD-1 expression on peripheral blood CD8+ T cells in a cohort of 27 melanoma patients, 11 breast cancer patients, and 30 non-Hodgkin lymphoma patients who ranged from having a normal body weight to having obesity ( 30 ). Our own examination of treatment-naive renal cancer patients found that higher plasma leptin concentrations were associated with reduced frequencies of peripheral blood PD-1+CD8+ T cells; in this patient cohort higher BMIs were also associated with reduced frequencies of activated CD45RO+CD8+ T cells ( 31 ).…”
Section: Obesity-associated Changes In Anti-tumor Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…The PD1-mediated T cell dysfunction in obesity could explain better outcomes for patients with obesity treated with ICIs (Wang et al 2019). However, these results were not confirmed by Khojandi et al that found no associations between BMI, leptin levels and PD1 expression on CD8 + tumorinfiltrating lymphocytes in a mixed cohort of melanoma and breast cancer patients (Khojandi et al 2021).…”
Section: :7mentioning
confidence: 85%